STUDENTS’ PERCEPTION OF THE USE OF STORY TELLING TECHNIQUE TO IMPROVE PRONUNCIATION SKILL - Nukmatus Syahria (IJET (Indonesian Journal of English Teaching), 2016)
The complexities of skills in the Pronunciation created many hindrances for the students in mastering the Pronunciation Practice subject. Most of the first semester students of Adi Buana University were failed during the mid test since they have very little background knowledge of the Pronunciation skills and they tend to get bored during the teaching and learning activities. The writer tried to apply the story telling technique in the middle of the semester to foster the pronunciation skills to the first semester undergraduate students of English Department as well as to arouse the students’ motivation in learning pronunciation. The writer used questionnaire to collect the data and each item in the questionnaire was analyzed and calculated then presented in the percentage to find out the students’ perception toward the use of story-telling technique. The result showed a significant progress on the final test score of the students and it also gave a good impact toward the students’ motivation in learning Pronunciation.